2021
DOI: 10.21873/anticanres.14991
|View full text |Cite
|
Sign up to set email alerts
|

PBK Expression Is Associated With Prognosis of Patients With Oral Squamous Cell Carcinoma Treated With Radiotherapy: A Retrospective Study

Abstract: Background/Aim: To investigate the impact of PDZ-binding kinase (PBK) on the clinical outcome of patients with oral squamous cell carcinoma (OSCC) who received radiotherapy. Patients and Methods: PBK immunoreactivity of cancer specimens obtained from 179 patients with primary OSCC was analyzed by immunohistochemistry. Results: High PBK expression in tumor cells tended to be associated with advanced N-stage. The 5-year survival rate was greater for patients with high total PBK expression than in those with low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Although previous studies [1,26,27] have reported higher expression of the PBK/TOPK mRNA and protein in tumor tissues than in adjacent noncancerous tissues from different tumors, this study was the first pan-cancer analysis of PBK/ TOPK and enabled us to observe the expression across all cancers. We only detected lower PBK/TOPK mRNA expression in LAML tissues than in normal tissues, which has not been reported in previous studies, although PBK/TOPK may mediate cell proliferation and viability in promyelocyte cell lines [28].…”
Section: Discussionmentioning
confidence: 90%
“…Although previous studies [1,26,27] have reported higher expression of the PBK/TOPK mRNA and protein in tumor tissues than in adjacent noncancerous tissues from different tumors, this study was the first pan-cancer analysis of PBK/ TOPK and enabled us to observe the expression across all cancers. We only detected lower PBK/TOPK mRNA expression in LAML tissues than in normal tissues, which has not been reported in previous studies, although PBK/TOPK may mediate cell proliferation and viability in promyelocyte cell lines [28].…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, PBK promotes cell migration by regulating phosphatidylinositol 3-kinase (PI3K)/phosphatase and tensin homolog (PTEN)/protein kinase B (AKT) or transforming growth factor beta 1 (TGF-β1)/mothers against decapentaplegic (Smad) signaling pathways ( Shih et al, 2012 ; Lee et al, 2020 ). PBK is differentially expressed between cancer and normal tissues and modulates radiosensitivity in tumors, suggesting that patients can be treated with radiotherapy ( Pirovano et al, 2017 ); and a recent retrospective analysis showed that PBK expression was negatively correlated with the prognosis of patients with oral squamous cell carcinoma treated with radiotherapy ( Yu et al, 2021 ). The PBK inhibitor OTS964/OTS514 was shown to inhibit cytokinesis and cancer cell growth ( Matsuo et al, 2014 ), and OTS964/OTS514 induced the apoptosis of lung cancer cells including small cell lung cancer (SCLC) cells ( Park et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…PBK was initially identified as a serine/threonine protein kinase for mitogen-activated protein kinase and is associated with cytokinesis and spermatogenesis[ 64 ]. PBK has been suggested as a promising prognostic predictor for patients with oral squamous cell carcinoma treated with radiotherapy[ 65 ]. PBK can enhance aggressive phenotypes of cervical cancer by regulating the ERK/c-Myc signaling pathway[ 66 ].…”
Section: Discussionmentioning
confidence: 99%